Dimensions of organizational immunity and its relationship Enhancing the strategic capabilities of the company: applied research in the Iraqi General Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to diagnose the nature of the relationship between the dimensions of organizational immunity with its dimensions represented by (organizational memory, organizational DNA, organizational learning) in enhancing the strategic capabilities of the company with its dimensions represented by (marketing capabilities, administrative capabilities, technological capabilities, creative capabilities), and the degree of arrangement of those dimensions According to priority, as well as revealing the differences in the respondents’ response to the two variables according to the personal and functional variables, and the importance of the expected results, the researchers adopted the questionnaire as a tool for collecting data from the members of the research community, which numbered (55) respondents from officials at the administrative levels (higher, middle, and lower levels). ), as the statistical program SPSS V.28) was used to calculate (weighted mean, standard deviation, relative importance, coefficient of variation, Pearson correlation coefficient), and the most prominent findings of the research are: There is a correlation between organizational immunity and strategic capabilities. For the company, the strongest correlation was the organizational learning dimension, as well as the absence of significant statistically significant differences in the respondents’ response to the Change the research due to personal and functional variables represented by (gender, age, educational qualification, administrative level, number of years of service